The Digital Frontier: How Computers Are Shaping the Future of Space Exploration - V. Basil Hans (International Journal of Satellite Remote Sensing, 2025)
The integration of computers and space technology has revolutionized the way we explore and understand space. Advanced computing systems play a pivotal role in space missions, from spacecraft navigation and communication to data processing and analysis. These technologies enable accurate modelling, simulation, and mission planning, allowing scientists and engineers to overcome the challenges of space exploration. Computers have also facilitated innovations such as artificial intelligence in autonomous spacecraft and real-time monitoring systems. This article explores the synergy between computers and space technology, examining the critical contributions of computational power in satellite operations, space telescopes, robotic exploration, and deep space missions. By analysing current advancements and future trends, the paper highlights how the evolving relationship between computers and space technology is shaping the future of space exploration.
Keywords: Current advancements; satellite system; space exploration; space radiation